Comparative studies on the intestinal health of wild and cultured ricefield eel (Monopterus albus) - Yang, Hang; Yuan, Quan; Rahman, Mohammad Mizanur; Lv, Weiwei; Huang, Weiwei; Hu, Wei; Zhou, Wenzong (Frontiers in Immunology, 2024)
Fish intestinal health under intensive aquaculture mode plays an important role in the growth, development and immune function. The present study was aimed to systematically investigate the differences of intestinal health between wild and cultured Monopterus albus by biochemical parameters, histomorphology and molecular biology. Fifteen healthy M. albus per group with average body weight of 45 g were sampled to analyze intestinal health parameters. Compared with the wild fish, the cultured M. albus in foregut had lower trypsin, lipase, SOD, CAT and T-AOC and GSH-Px activities (P<0.05), and higher amylase activity and MDA content (P<0.05). The villus circumferences and goblet cells in cultured group were significantly lower than those in wild group (P<0.05). In addition, the cultured fish showed lower relative expression levels of occludin, zo-1, zo-2, claudin-12, claudin-15, mucin5, mucin15, lysozyme, complement 3, il-10, tgf-β1, tgf-β2 and tgf-β3 (P<0.05), and higher il-1β, il-6, il-8, tnf-a and ifnγ mRNA expressions than those of wild fish (P<0.05). In term of gut microbiota, the cultured group at the phylum level displayed higher percentages of Chlamydiae and Spirochaetes, and lower percentages of Firmicutes, Bacteroidetes, Actinobacteria, Cyanobacteria and Verrucomicrobia compared to the wild group (P<0.05). At the genus level, higher abundances of Pseudomonadaceae_Pseudomonas and Spironema, and lower abundances of Lactococcus and Cetobacterium were observed in the cultured group than wild group (P<0.05). To our knowledge, this is the first investigation of the intestinal health status between wild and cultured M. albus in terms of biochemistry, histology, and molecular biology levels. Overall, present study showed significant differences in intestinal health between wild and cultured M. albus, and the main manifestations that wild M. albus had higher intestinal digestion, antioxidant capacity, and intestinal barrier functions than cultured M. albus. These results would provide theoretical basis for the subsequent upgrading of healthy aquaculture technology and nutrient regulation of intestinal health of cultured M. albus.